Identification of Single Nucleotide Polymorphisms Related to the Resistance Against Acute Hepatopancreatic Necrosis Disease in the Pacific White Shrimp Litopenaeus vannamei by Target Sequencing Approach - Zhang, Qian; Yu, Yang; Wang, Quanchao; Liu, Fei; Luo, Zheng; Zhang, Chengsong; Zhang, Xiaojun; Huang, Hao; Xiang, Jianhai; Li, Fuhua (Frontiers in Genetics, 2019)
Acute hepatopancreatic necrosis disease (AHPND) is a major bacterial disease in the Pacific white shrimp Litopenaeus vannamei (L. vannamei) farming, which is caused by Vibrio parahaemolyticus (V. parahaemolyticus). It has led to a significant reduction of shrimp output since its outbreak. Selective breeding for disease resistance broodstocks is regarded as a key strategy for solving the disease problem. Understanding the relationship between genetic variance and AHPND resistance is the basis for marker-assisted selection (MAS) in shrimp. The purpose of this study is to identify the single nucleotide polymorphisms (SNPs) associated with the resistance against AHPND in L. vannamei. In this work, two independent populations were used for V. parahaemolyticus challenge and the resistant or susceptible shrimp were evaluated according to the survival time after Vibrio infection. The above two populations were genotyped separately by a SNP panel designed based on the target sequencing platform using a pooling strategy. The SNP panel contained 508 amplicons from DNA fragments distributed evenly along the genome and some immune related genes of L. vannamei. Through analyzing the allele frequency in the resistant and susceptible groups, 30 SNPs were found to be significantly associated with the resistance of the shrimp against V. parahaemolyticus infection (FDR corrected at P< 0.05). Three SNPs were further validated by individual genotyping in all samples of population 1. Our study illustrated that target sequencing and pooling sequencing were effective for identifying the markers associated with economic traits, and the SNPs identified in this study could be used as molecular markers for breeding disease resistance shrimp.